Kemampuan Koneksi Matematis Antar Topik Matematika: Analisis Kesalahan Jawaban Siswa Sekolah Dasar - Amalia, Lis; Septaliana, Trilius (Universitas Muhammadiyah Palembang, 2021)
Mathematical connection ability is a requirement that elementary school students must have in the learning process. But in reality there are still many students who do not have and have not hone this ability well. Elementary school students often make mistakes in solving math problems, especially about mathematical connections between math topics. There are different types of errors and the causes of these problems can occur. Therefore, an analysis of these errors is very important to do in order to see the root of the problem and find solutions that can be done. In this study, data were obtained from student answer sheets from written tests and information obtained from interviews with students in class V as many as 20 people. The research itself is in the form of qualitative descriptive research. From the results of the analysis, it can be summarized that there were several mistakes made by students including students who did not understand the context of the problem, misinterpreted the questions, made mistakes in mathematical modeling, the ability to present material and information from questions that were not good. This information is important as input for making improvements to the next teaching pattern.